Commodity Exchange and Stock Exchange in Islamic Economy - Muhammad Akram Khan (International Institute of Islamic Thought, 1988)
Introduction The main objective of this paper is to review contemporary practices in commodity, currency and corporate stock trading in the light of Islamic economic framework and to suggest bare outlines of the Islamic alternatives in these areas. Trade in commodities, currencies and stocks involves forward and htures contracts. Arbitrage, hedging and speculation are also essential elements of these markets. We shall try to examine these practices to determine their compatibility with the Islamic law. We shall also try to find out the exact point where they deviate from the Islamic framework and suggest some mechanism to perform the same economic function in the Islamic economy. Our main conclusions are summarized below: First, by and large the trade in spot and forward markets is covered by the Islamic law. Second, futures trading is alien to the Islamic law as it involves trading without actual transfer of the commodity or stock to the buyer which is explicitly prohibited by the Prophet (SAAS). Third, speculation by itself is not unlawful in Islam but the Islamic economic framework does not allow professional speculators to thrive. Fourth, the Islamic condition of transfer of the commodity stock to the buyer is a mechanism to boost the real sector. Fifth, stability in the foreign exchange market can be achieved by cooperation of the international community. It would necessitate abolition of al riba and scrapping of trade restrictions over borders besides accepting money as a medium of exchange only, rather than a commodity. Sixth, to discourage negative effects of speculation, information regarding commodities and corporations needs to be widely and freely disseminated. No amount of restrictive regulations can ...